2020
DOI: 10.1161/strokeaha.119.026128
|View full text |Cite
|
Sign up to set email alerts
|

Noncontrast Computed Tomography Signs as Predictors of Hematoma Expansion, Clinical Outcome, and Response to Tranexamic Acid in Acute Intracerebral Hemorrhage

Abstract: Background and Purpose— Blend, black hole, island signs, and hypodensities are reported to predict hematoma expansion in acute intracerebral hemorrhage. We explored the value of these noncontrast computed tomography signs in predicting hematoma expansion and functional outcome in our cohort of intracerebral hemorrhage. Methods— The TICH-2 (Tranexamic acid for IntraCerebral Hemorrhage-2) was a prospective randomized controlled trial exploring the efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 22 publications
3
51
2
Order By: Relevance
“…Li et al [9] found that black hole sign could predict poor outcome in ICH. Law et al [19] demonstrated that black hole sign was a subset of hypodensities, which is consistent with our results. We also observed the overlap of black hole sign and hypodensities in this study.…”
Section: Discussionsupporting
confidence: 94%
“…Li et al [9] found that black hole sign could predict poor outcome in ICH. Law et al [19] demonstrated that black hole sign was a subset of hypodensities, which is consistent with our results. We also observed the overlap of black hole sign and hypodensities in this study.…”
Section: Discussionsupporting
confidence: 94%
“…The majority of the studies were conducted in China. Therefore, the conclusions are representative of the Chinese population at large, and similar results were not observed among Malaysians (15). The discrepancy may account, at least in part, for the diagnostic criteria.…”
Section: Discussionsupporting
confidence: 61%
“…Island sign is defined as (1) three or more scattered small hematomas all separated from the main hematoma, or (2) four or more small hematomas some or all of which may be connected with the main hematoma. Some investigations have reported that IS can predict the prognosis of ICH (11)(12)(13)(14), whereas others have reported that there was no significant correlation between IS and HE (15). There is insufficient evidence to declare that IS is an independent predictor for ICH patients' prognosis and classification.…”
Section: Introductionmentioning
confidence: 98%
“…Measurements of hematoma, intraventricular hemorrhage and perihematomal edema (PHE) volumes were performed by three independent raters blinded to clinical data using semi-automated segmentation tools of ITK-SNAP software version 3.6.0 [ 13 , 14 ]. Radiological adjudication including location of hematoma and presence of IVH was performed by a group of qualified neuroradiologists.…”
Section: Methodsmentioning
confidence: 99%